Optimization of succinic acid production from immobilized escherichia coli - Nik Nor Aziati, Abd Aziz (2018)
Succinic acid can be produced from glycerol residue by fermentation of immobilized Escherichia coli. Increament of the price of succinic acid is one of the factors to produce the succinic acid from the waste of glycerol. As a by product of oleochemical production, glycerol has now become an abundant and cheap source of carbon. To reduce the production cost, the glycerol waste is an alternative substrate for succinic acid production. Besides, by using immobilization method, the cells can be reused for succinic acid production.Therefore, this study was aimed to produced succinic acid using glycerol recovered from industrial waste oleochemicals, with E. coli that have been immobilized. Comparison between fermentation process using free and immobilized E-coli is carried out by considering the mass of the substrate, the density of inoculum and fermentation time. Succinic acid that has been produced from immobilized cell fermentation was optimized using response surface methodology. The study also identified the characteristics of immobilized cells including cell stability and the ability to recycle beads during the fermentation process. High performance liquid chromatography was used to analyze the concentration of glycerol and succinic acid. While Fourier transform infrared spectroscopy was used to analyze the functional groups of glycerol. One of the main studies was the kinetic study of the free and immobilized cells, which studied the effect of the substrate on the growth profile of the microorganism and thus, the production of succinic acid. The results obtained for the maximum specific growth rate μmax (hr-1) was 0.031 h-1 and the KS was 5.11 g for the immobilized cells, while for the free cells, the maximum growth rate was 0.029 h-1 and KS of 4.03 g. The difference between the immobilized and free cells was about 6.9 % for the μmax (hr-1) and 26.8 % for the KS. The results proved that the substrate concentration is one of the factors that may affect the microorganism growth rate. To optimize the parameters for scale-up purposes the optimum conditions observed for succinic acid fermentation process were time 3.31 h, mass substrate 40 g, and inoculum density 15%. At these optimum conditions, 124.09 g/L of succinic acid was obtained. The total yield obtained was 5.95 g of succinic acid. This study was successfully developed to produce and improve the succinic acid production from renewable glycerol residue using the immobilized cell method. For the immobilized cells, the selection method was important for high production of succinic acid. To reduce the cost of succinic acid production, the immobilized cells have the advantage of been able to be reused up to 6 cycles for succinic acid production. A further study should be carried out to investigate the structure of the beads for high production of succinic acid using the entrapment method.